Child Abuse Experiences and Perceived Need for Care and Mental Health Service Use among Members of the Canadian Armed Forces. (June 2017) - Turner, Sarah; Taillieu, Tamara; Cheung, Kristene; Zamorski, Mark; Boulos, David; Sareen, Jitender; Afifi, Tracie O.
Objective: Child abuse is associated with poor mental health outcomes in adulthood. However, little is known about how a history of child abuse may be related to perceived need for care (PNC) and mental health service use (MHSU) among Canadian military personnel. The objectives of this study were to determine 1) the relationship between child abuse history and PNC and 2) the relationship between child abuse history and MHSU in the Canadian military. Method: Data were drawn from the 2013 Canadian Forces Mental Health Survey ( n = 6692 Regular Force personnel between the ages of 18 and 60 years). Logistic regression was used to examine the relationships between individual child abuse types and PNC and MHSU while adjusting for sociodemographic variables, the presence of mental disorders, deployment-related variables, and other types of child abuse. Population attributable fractions (PAFs) were calculated to estimate the proportion of PNC and MHSU that may be attributable to child abuse. Results: Each individual child abuse type was associated with increased odds of PNC and MHSU after adjusting for all covariates (adjusted odds ratio ranging from 1.26 to 1.80). PAFs showed that if any child abuse did not occur, PNC and MHSU among Regular Force personnel may be reduced by approximately 14.3% and 11.3%, respectively. Conclusions: This study highlights that preenlistment factors, such as a history of child abuse, have an independent association with PNC and MHSU and hence need to be considered when assessing the mental health service needs of the Canadian Regular Force personnel.